1140. GATA2 Mutations Are Frequently Identified Among Patients With Myeloid Malignancies Who Develop Invasive Aspergillosis. (26th November 2018) - Bold, Tyler D; Cheng, Matthew P; Vedula, Rahul S; Marty, Francisco M; Lindsley, R Coleman
Abstract: Background: Patients with myeloid malignancies are at risk of invasive aspergillosis (IA), a cause of significant morbidity and mortality. Identification of patients at higher risk for IA may help optimize prophylactic or preemptive treatment decisions. Molecular genetic testing used to risk-stratify and guide therapy for hematologic malignancies may also have applicability toward predicting infectious outcomes. The purpose of this study was to identify mutations that may increase risk for IA among patients with myeloid malignancies. Methods: We identified patients cared for at Dana-Farber/Brigham and Women's Cancer Center between March 1, 2015 and January 31, 2018 who were diagnosed with probable or proven IA during the treatment of myeloid malignancies including acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS). We reviewed pathogenic mutations detected by the Rapid Heme Panel (RHP), a clinical targeted next-generation sequencing panel of 95 recurrently mutated genes in hematologic malignancies. Results: Twenty-four patients with myeloid malignancy (AML 20, MDS 4) were diagnosed with IA, 20 of whom (AML 17, MDS 3) had undergone genetic testing with the RHP at the time of their cancer diagnosis. We found that three of 20 patients (15%) had a pathogenic mutation in GATA2 . All were missense mutations within the functional zinc-finger domains, including one resulting in an R398W amino acid change, one of the spectrum of germline mutations known to cause the primary immunodeficiency MonoMAC. Patients with GATA2 mutations in our cohort were ages 35–68 and variant allele fraction ranged from 16.3% to 49.7%, raising the possibility that both inherited and acquired GATA2 dysfunction could incur a similar infectious risk. Conclusion: Mutations in GATA2, a gene associated with MonoMAC syndrome, were common among patients with myeloid malignancy who developed IA. These data suggest that personalized genetic analyses of patients with underlying hematologic malignancy may also be useful for assessment of infectious risk. Disclosures: All authors: No reported disclosures.